Ants of North America : a Guide to the Genera. - Fisher, Brian L. (University of California Press, 2007)
Ants are among the most conspicuous and the most ecologically important of insects. This concise, easy-to-use, authoritative identification guide introduces the fascinating and diverse ant fauna of the United States and Canada. It features the first illustrated key to North American ant genera, discusses distribution patterns, explores ant ecology and natural history, and includes a list of all currently recognized ant species in this large region. * New keys to the 73 North American ant genera illustrated with 250 line drawings ensure accurate identification * 180 color images show the head.